Variations in the Urinary Iodine Concentration and Urinary Iodine/Creatinine Ratio among Preschool Children - Dong An; Rui Yang; Yuping Du; Xuan Wang; Ying Yang; Wenxing Guo; Junhong Yang; Dongmei Meng; Weiwei Gao; Jiayi Zhang; Wen Chen; Wanqi Zhang (International Journal of Endocrinology)
Variations in different urinary measurements for evaluating iodine status are concerning to clinicians and researchers. The present study aimed to analyze the interindividual and intraindividual variations in the urinary iodine concentration (UIC) and urinary iodine/creatinine (UI/Cr) ratio and evaluate their application in assessing the iodine nutrition of preschool children. Four repeated spot urine samples were collected from 163 children at different times within one day. The urinary iodine concentration (UIC) and urinary creatinine concentration (UCr) were measured, and the UI/Cr ratio was calculated. The UIC (P < 0.001) and urinary iodine/creatinine ratio (P = 0.019) of multiple measurements were significantly different. The UIC of morning urine was highest (99.83 μg/L) and then gradually decreased with collection time (P < 0.001). In contrast, the UI/Cr ratio of morning urine samples increased with collection time. By computing the mean intraindividual and interindividual coefficients of variance (CV), the intraindividual variation of the UI/Cr ratio (68%) was significantly lower than that of the UIC (86%). Nevertheless, the interindividual variation was lowest in the UIC (78.62%) of morning urine. In addition, the UIC and UI/Cr ratio showed moderate correlations (r = 0.52, P < 0.001), with kappa values of 0.42 in assessing iodine nutrition. The UIC of morning urine samples taken at 8:00–10:00 am was perhaps more stable and reliable in evaluating the iodine nutrition of preschool children at the population level. The UI/Cr ratio showed lower intraindividual variation and may be more suitable for assessing individual iodine nutrition.